Institutional Design of the Corruption Eradication Commission (KPK) Post-Constitutional Court Decisions Number 70/PUU-XVII/2019 and Number 79/PUU-VII/2019 - al Arif, M. Yasin (Universitas Islam Negeri Raden Intan Lampung, 2023)
Following the ratification of Law Number 19 of 2019 concerning the Corruption Eradication Commission, many parties were disappointed with the institutional design constructed in that law. Therefore, a judicial review was filed against the law with the Constitutional Court. This article aims to understand the institutional design of the Corruption Eradication Commission after the issuance of Constitutional Court Decisions Number 70/PUU-XVII/2019 and Number 79/PUU-VII/2019. In case Number 70/PUU-XVII/2019, the petitioner not only submitted a request for material testing but also a formal request, while in case Number 79/PUU-VII/2019, the petitioner only submitted a request for material testing. This paper seeks to answer two important questions: what are the legal consequences of Constitutional Court Decisions Number 70/PUU-XVII/2019 and Number 79/PUU-VII/2019? And what is the institutional design of the Corruption Eradication Commission following the issuance of Constitutional Court Decisions Numbers 70/PUU-XVII/2019 and Number 79/PUU-VII/2019? The study concludes that the consequences of these Constitutional Court decisions, including wiretapping, searches, and/or seizures carried out by the Corruption Eradication Commission, do not require permission from the Supervisory Board. The transition process of the Corruption Eradication Commission's employee status should not disadvantage anyone, and the two-year time calculation in case of investigation termination starts from the issuance of the Investigation Initiation Letter (SPDP). The institutional design of the Corruption Eradication Commission established after this decision includes the position of the Corruption Eradication Commission in the state institutional structure, the position of the Corruption Eradication Commission's employees, and the authority of the Corruption Eradication Commission's Supervisory Board.